On the development of twinning-induced plasticity in additively manufactured 316L stainless steel - D. Della Crociata; I. Maskery; R. Hague; M. Simonelli (Additive Manufacturing Letters, 2023)
A report on twinning-induced plasticity in 316L stainless steel manufactured by metal additive manufacturing (AM) is presented. A tapered tensile test geometry was used which enabled the investigation of twin formation over a range of strain levels in a single specimen. Hardness and twinning concentration were observed to increase with strain up to peak values of 380 ± 10 HV and 28 ± 4%, respectively. Furthermore, twin formation was found to be regulated by grain size and crystal texture. This methodology can be applied to new AM materials development and will inform the design of energy-absorbing structures that maximise the benefits of AM design and strain-hardenable materials.